Definitions of Agile Software Development and Agility - and Laanti, Maarit; Similä, Jouni; Abrahamsson, Pekka (Springer, 2013)
The Agile Manifesto and Agile Principles are typically referred to as the definitions of "agile" and "agility". However, many other definitions exist in the literature. Thus the different definitions provide interesting source for research. For each definition we examine where their emphasis is and compare that to the emphases found in the Agile Principles.